Together towards Life, Missional Formation, and Transforming Discipleship - Ross, Kenneth R. ca. 20./21. Jh. (2017)
Adoption of Together towards Life as a new mission statement of the World Council of Churches was a moment pregnant with possibility. Will this ground-breaking document have a transformative impact on individual lives, on community life, on national life, on international life? The answer, to a great extent, will depend on how far it comes to be used as a resource in education and formation. For it to be used in a relevant and effective way, it will need to be considered contextually. A project has been under way to create a pedagogical guidebook to support the deployment of Together towards Life in missional education and formation. This will promote academic rigour, but will also go further to engage the spiritual level and the challenge of discipleship.